STRATEGI PENDIDIKAN SEBAYA MENINGKATKAN KESEHATAN REPRODUKSI REMAJA DI PESANTREN - Roikhatul Jannah Jannah (Poltekkes Kemenkes Jakarta III, 2014)
In the last decades, health agents have been exploring and developing adolescent sexual reproductive health initiative in respon various sexual reproductive health cases among young people. This study aims to observe how effective peer education strategy to improve awareness as well as reproductive health knowledge among young people in pesantren. This research is qualitative approach that utilized ethnographic perspective for interpreting the result. By analyzing final report of the implemented initiatives in pesantrens, the result of this study shows that peer education strategy is effective, applicable, manageable, and modifiable for educating santri's reproductive health as long as health agents success inlobbing the pesantren leader, the Kyai. Conclusion: Peer education concept which is culturally sensitive is proofed and recommended in adolescent sexual reproductive health (ASRH) initiative development for pesantren's student when it it is able to blended and integrated with activities of santris.